Sistem Informasi Evaluasi Kinerja Manajemen SDM menggunakan Key Performance Indicator pada PT. X - Kurnia, Rahma; Nurlani, Lani; Perdana, Chepy (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
The Company's HR performance measurement system can be carried out by implementing the Human Resource Scorecard approach where the Company can determine measurable and relevant indicators in accordance with the Company's strategic objectives from various perspectives, internal business processes, HR Alignment, and HR Deliverable (Learning & Growth). This research aims to see the achievement of targets imposed on an organization using the Key Performance Indicator (KPI) instrument. The results of this research show that there are 4 perspectives, namely HR Efficiency (Financial), High Performance Work System Perspective (Internal Business Process), HR Engagement (Customer), and HR Deliverable (Learning & Growth). From these four perspectives there are 9 indicators used to build an HR performance evaluation system that is in accordance with PT. X. The system built can show the achievement value of each indicator which can be evaluated to determine Company policy. This system is equipped with a traffic light system which can show information about which indicators need improvement, need to be improved, and are in line with targets.